Brain Structure Alterations in Hemifacial Spasm: A Diffusion Tensor Imaging Study. (March 2022) - Zhang, Jian; Yu, Qingyang; Gu, Peng; Sun, Hongtao; Yuan, Fei; Zhang, Quan
This study examined white matter integrity in patients with left-sided hemifacial spasm (HFS) using diffusion tensor imaging (DTI). Thirty-six patients with left-sided HFS (mean age 53.24 ± 8.16 years) and 36 healthy volunteers (mean age 53.92 ± 7.73 years) were recruited. Tract-based spatial statistics (TBSS) analysis revealed significantly increased fractional anisotropy (FA) of bilateral superior longitudinal fasciculus in HFS patients ( P < 0.05, family-wise error corrected), with trends for radial diffusivity to decrease. We inferred that the results may be associated with poor sleep quality, impairment in visuospatial construction, and activity-dependent increases in myelination in HFS patients. Furthermore, the FA value of left superior longitudinal fasciculus showed a positive correlation with HFS duration ( r = 0.352, P = .041) and spasm severity ( r = 0.416, P = .014). However, the alteration of medial diffusivity and axial diffusivity were not found in bilateral superior longitudinal fasciculus between groups. These findings suggest FA changes of superior longitudinal fasciculus reflected by TBSS analysis may provide valuable insights into the diagnosis of HFS.